2007
DOI: 10.1111/j.1447-0756.2007.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionized and total magnesium concentration in patients with severe preeclampsia‐eclampsia undergoing magnesium sulfate therapy

Abstract: Despite the effectiveness of the standard regimen of magnesium sulfate in the treatment and prevention of eclamptic seizures, it can not provide the proposed therapeutic level of magnesium in all patients. With respect to the lack of correlation between ionized and total magnesium, further studies are necessary to investigate the superiority of measurement of ionized, rather than total magnesium, for titration of therapeutic magnesium sulfate infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 21 publications
2
30
2
Order By: Relevance
“…Of note, the studied group did not suffer from obesity. HDMI pharmacokinetic have shown magnesium serum levels associated with smooth muscle relaxation but a need of adjustment in patients with obesity (9,10,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the studied group did not suffer from obesity. HDMI pharmacokinetic have shown magnesium serum levels associated with smooth muscle relaxation but a need of adjustment in patients with obesity (9,10,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…13 While the amount of iMg capable of producing relaxation is not completely understood, recent reports for preeclampsia describe target values of 0.9 to 1.6 mmol/L. 4,[14][15][16] The asthma literature is hesitant to target dosing that achieves decreases in reflexes for fear of inducing respiratory failure due to decreased respiratory muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium sulfate's spasmolytic effect, when administered as a continuous infusion, has been used in patients with preeclampsia, pulmonary hypertension, brain injury, and subarachnoid hemorrhage. [4][5][6][7] In these settings, the strategy of continuous infusion produces a sustained effect by exceeding the rate of magnesium elimination by the kidney. A sustained effect may be the one desirable effect for asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al (2007) reported that magnesium sulfate has no effect on sever preeclampsia and eclampsia patients. They suggested that protective drug regimen is not associated with changes in serum calcium levels 30 . However, various studies reported controversial results on serum calcium level in preeclamptic patient compared to individuals with normal blood pressure and there are still some ambiguities 7-10, 31, 32 .…”
Section: Discussionmentioning
confidence: 99%